Letter (copy) : Aid for Spain - Citrine, Walter, 1887-1983
012a-0042-001 International. WMC/WJB/EAB. 15th September 1938. Union General de Trabajadores de España, Avda, del 14 April, 423, Dear Comrades, Aid for Spain. We duly received your letter dated the 27th August, and thank you most heartily for the wishes expressed therein with regard to the deliberations of our Congress. Our General Council decided to read your communications to the assembled delegates. You can rest assured that the British Trade Unions will continue to do all that is possible to help their fellow Trade Unionists in Spain, in order that eventually success may crown the struggle you and your comrades are so heroically making against the Fascist rebels. Yours sincerely, General Secretary. 292/946/12a/42